2016
DOI: 10.1007/978-3-319-33461-5_12
|View full text |Cite
|
Sign up to set email alerts
|

Popular Edges and Dominant Matchings

Abstract: Abstract. Given a bipartite graph G = (A ∪ B, E) with strict preference lists and e * ∈ E, we ask if there exists a popular matching in G that contains the edge e * . We call this the popular edge problem. A matching M is popular if there is no matching M such that the vertices that prefer M to M outnumber those that prefer M to M . It is known that every stable matching is popular; however G may have no stable matching with the edge e * in it. In this paper we identify another natural subclass of popular matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(77 citation statements)
references
References 16 publications
0
77
0
Order By: Relevance
“…Note that there is a one-to-one correspondence between branchings in G and arborescences in D (simply make r the parent of all roots of the branching). A branching is popular in G if and only if the corresponding arborescence is popular among all arborescences in D. 9 We will therefore prove our results for arborescences in D. The corresponding results for branchings in G follow immediately by projection, i.e., removing node r and its incident edges.…”
Section: Dual Certificatesmentioning
confidence: 66%
“…Note that there is a one-to-one correspondence between branchings in G and arborescences in D (simply make r the parent of all roots of the branching). A branching is popular in G if and only if the corresponding arborescence is popular among all arborescences in D. 9 We will therefore prove our results for arborescences in D. The corresponding results for branchings in G follow immediately by projection, i.e., removing node r and its incident edges.…”
Section: Dual Certificatesmentioning
confidence: 66%
“…The augmentation of G into G * is based on a certain subgraph of G called its "popular subgraph". Call an edge e in G = (A ∪ B, E) popular if there is some popular matching in G that contains e. Let E F ⊆ E be the set of popular edges in G. The set E F can be computed in linear time, see [11]. Call F G = (A ∪ B, E F ) the popular subgraph of G.…”
Section: The Popular Subgraphmentioning
confidence: 99%
“…[11]). A popular matching M in G = (A ∪ B, E) is dominant if and only if M admits a witness α such that α v ∈ {±1} for every popular vertex v.…”
mentioning
confidence: 99%
“…Dominant matchings always exist in a bipartite graph and such a matching can be computed in linear time [18]. Every polynomial time algorithm currently known to find a popular matching in a bipartite graph finds either a stable matching [9] or a dominant matching [14,18,7].…”
Section: Definitionmentioning
confidence: 99%
“…For instance, Kavitha [18] showed that a max-size popular matching can be found efficiently by a combination of the Gale-Shapley algorithm and promotion of nodes rejected once by all neighbors. Cseh and Kavitha [7] showed that a pair of nodes is matched together in some popular matching if and only if this pair is matched together either in some stable matching or in some dominant matching. Dominant matchings are a subclass of max-size popular matchings, and these are equivalent (under a simple linear map) to stable matchings in a larger graph.…”
Section: Introductionmentioning
confidence: 99%